The Use of a DNA-Intercalating Dye for Quantitative Detection of Viable Arcobacter spp. Cells (v-qPCR) in Shellfish - Salas-Massó, Nuria; Linh, Quyen Than; Chin, Wai Hoe; Wolff, Anders; Andree, Karl B.; Furones, M. Dolors; Figueras, María José; Bang, Dang Duong (Frontiers in Microbiology, 2019)
The genus Arcobacter (Vandamme et al., 1991), comprised of Campylobacter-related species, are considered zoonotic emergent pathogens. The presence of Arcobacter in food products like shellfish, has an elevated incidence worldwide. In this study we developed a specific viable quantitative PCR (v-qPCR), using the dye propidium monoazide (PMA), for quantification of the viable Arcobacter spp. cells in raw oysters and mussels. The high selectivity of primers was demonstrated by using purified DNA from 38 different species, 20 of them from the genus Arcobacter. The optimization of PMA concentration showed that 20 μM was considered as an optimal concentration that inhibits the signal from dead cells at different concentrations (OD550 from 0.2 to 0.8) and at different ratios of live: dead cells (50:50 and 90:10). The v-qPCR results from shellfish samples were compared with those obtained in parallel using several culture isolation approaches (i.e. - direct plating on marine and blood agar and by post-enrichment culturing in both media). The enrichment was performed in parallel in Arcobacter-CAT broth with and without adding NaCl. Additionally, the v-qPCR results were compared to those obtained with traditional quantitative (qPCR). The v-qPCR and the qPCR resulted in c.a 94% of positive detection of Arcobacter vs. 41% obtained by culture approaches. When examining the reduction effect resulting from the use of v-qPCR, samples pre-enriched in Arcobacter-CAT broth supplemented with 2.5% NaCl showed a higher reduction (3.27 log copies) than that of samples obtained directly and those pre-enriched in Arcobacter-CAT broth isolation (1.05 and 1.04). When the v-qPCR was applied to detect arcobacter from real shellfish samples, 15/17 samples tested positive for viable Arcobacter with 3.41 to 8.70 log copies 1g-1. This study offers a new tool for Arcobacter surveillance in seafood.